INTEGRATOR PLATFORM MODEL TO SUPPORT MSME - Masripah Masripah; Alvita Yuniar; Meizaroh Meizaroh (Institute of Computer Science (IOCS), 2021)
This research focuses on designing an integrator platform called OperBisnis. This research attempts to answer questions about what kind of facilities are needed to support the collaboration between MSMEs and other parties. The method used was a descriptive approach. The results of the formation of OperBisnis show several benefits that can connect various parties such as banking institutions, mentors, investors, business incubators and accelerators, and others and form the function of education to funding.